ABDOMINOPLASTY IN A WOMAN AFTER A SIGNIFICANT WEIGHT LOSS - A. DAVLATOV; H. DODARIYON; G. AL OMER (Avicenna Tajik State Medical University, 2021)
In this paper, we wish to present a case report of a 38-year-old woman who underwent abdominoplasty (AP). Patient history obtained during the preoperative phase of care included sleeve gastroplasty, after which she noted a significant weight loss (about 35 kg). As a result, a saggy skin-fat flap of the abdomen in the form of an apron was formed. In addition, she was worried about the pronounced drooping and sagging breasts. Therefore, the patient was offered AP through combined vertical and horizontal incisions. However, due to the patient's refusal of the combined incisions, AP with a transverse incision and vertical mammoplasty were performed. A year later, dissatisfied with the cosmetic result, the patient insisted on AP through a combined incision, which was performed. At this time, the patient indicated her satisfaction with the aesthetic outcomes.